2022
DOI: 10.31234/osf.io/q6c9r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morality Beyond the WEIRD: How the Nomological Network of Morality Varies Across Cultures

Abstract: Moral Foundations Theory has been a generative framework in moral psychology in the last two decades. Here, we revisit the theory and develop a new measurement tool, the Moral Foundations Questionnaire-2 (MFQ-2), based on data from 25 populations. We demonstrate empirically that Equality and Proportionality are distinct moral foundations while retaining the other four existing foundations of Care, Loyalty, Authority, and Purity. Three studies were conducted to develop the MFQ-2 and to examine how the nomologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 99 publications
(140 reference statements)
3
69
1
Order By: Relevance
“…This collective response was striking, given the many differences in values and experiences between individuals within and across cultures, and is consistent with psychological and anthropological research documenting similarities in which behaviors are deemed morally right versus wrong across cultures (Brown 1991;Curry et al 2019;Graham et al 2011; see also, Atari et al 2022). For example, in examining the ethnographies of 60 societies worldwide, Curry et al (2019) found evidence across societies that behaviors such as helping and dividing resources equally are seen as morally good.…”
Section: Introductionsupporting
confidence: 72%
“…This collective response was striking, given the many differences in values and experiences between individuals within and across cultures, and is consistent with psychological and anthropological research documenting similarities in which behaviors are deemed morally right versus wrong across cultures (Brown 1991;Curry et al 2019;Graham et al 2011; see also, Atari et al 2022). For example, in examining the ethnographies of 60 societies worldwide, Curry et al (2019) found evidence across societies that behaviors such as helping and dividing resources equally are seen as morally good.…”
Section: Introductionsupporting
confidence: 72%
“…This reasoning closely parallels the logic of variations in authoritarian values (Nettle & Saxe, 2021), which are associated with puritanical values (Atari et al, 2022;Harper & Rhodes, 2021).…”
Section: Explaining the Fall Of Puritanismsupporting
confidence: 55%
“…Their most systematically documented pattern of variation is their decline in particularly rich, WEIRD societies. In line cultural psychological studies (Atari et al, 2022;Haidt et al, 1993;Shweder et al, 1987), the World Value Surveys demonstrate that virtually all societies, when they are made richer by modern economic development, progressively abandon puritanical values (Inglehart, 2018;Inglehart & Baker, 2000). The richest regions of the world (e.g., Western Europe, North America, Australia/New Zealand) show the lowest levels of puritanical values, while the poorest regions (e.g., Africa, Middle East, Communist Asia) exhibit the highest levels .…”
Section: Explaining the Fall Of Puritanismmentioning
confidence: 93%
See 1 more Smart Citation
“…We included additional measures, not used in the analyses reported in this paper, including measures of moral conviction (Ryan, 2014), gender-related systemjustifying beliefs (Jost & Kay, 2005), and the updated moral foundations questionnaire (Atari et al, 2022, for details, see SOM). Within the latter questionnaire, we embedded three further attention checks (e.g., "To show that you are paying attention and giving your best effort, please select 'moderately describes me' .…”
Section: Methodsmentioning
confidence: 99%